Is Long-Term Food Insecurity Inevitable in Asia - Cuesta, Jose (Taylor and Francis, 2014)
This article questions two widely accepted claims on long-term food insecurity in Asia, the world's (heterogeneous) region with the largest number of undernourished individuals. The first claim is that food production may not grow as fast as the pace of population growth in Asia, which will reach 5 billion by 2050. The second claim is that an unstoppable emergence of a middle class in Asia will dramatically change the composition of food demand. On the first claim, the region's contribution to high and volatile international food prices is well known, but Asia's potentially positive contributions toward future price uncertainty and productivity growth are much less cited. On the second claim, the changing composition of future food demand in the region will depend on the extent that poverty reduction effectively leads to middle class expansion, which it is not an automatic process, and its extent still remains to be seen. Past evidence teaches us that poverty reduction on its own will not do the job of eradicating hunger, nor will only increasing food production. The jury is still out, but doomsday predictions are not necessarily justified.